2010
DOI: 10.5312/wjo.v1.i1.26
|View full text |Cite|
|
Sign up to set email alerts
|

Return to sports activity by athletes after treatment of spondylolysis

Abstract: AIM:To clarify the efficacy of conservative and surgical treatment of spondylolysis in athletes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 26 publications
0
16
0
Order By: Relevance
“…Case series by Sys et al 28 and Iwamoto et al 8 each found a high percentage of return to sport (89.3% and 87.5%, respectively) with nonoperative treatment and bracing.…”
Section: Discussionmentioning
confidence: 96%
“…Case series by Sys et al 28 and Iwamoto et al 8 each found a high percentage of return to sport (89.3% and 87.5%, respectively) with nonoperative treatment and bracing.…”
Section: Discussionmentioning
confidence: 96%
“…145 In another series evaluating the outcomes of pars stress fractures in young athletes, the average time needed to return to sport was 5.4 months. 146 The decision regarding rigid antilordotic bracing remains controversial, though most of the athletes would agree that a period of rest, with or without bracing, until pain free is necessary. 147 Progression to spondylolisthesis of >20% occurs in only about 4% of cases over 7 years of follow-up.…”
Section: Spine ( Pars Interarticularis)mentioning
confidence: 99%
“…9,32 Unilateral defects have DISCUSSION t he positive short-term functional outcomes observed for the patients with acute spondylolysis in this study are similar to previously published work. 13,14,[24][25][26][27]45 At discharge, mean pain scores were relatively low (0.20  0.57), and 93% of patients were released to fully return to sport. One hundred percent of patients who were compliant with care were released to all aspects of sport.…”
Section: Limitationsmentioning
confidence: 99%